2019
DOI: 10.20944/preprints201907.0033.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Spectroscopy of Various Types of Gypsum: An ideal Terrestrial Analogue

Abstract: The first detection of gypsum (CaSO4.2H2O) by the Mars Science Laboratory (MSL) rover Curiosity in the Gale Crater, Mars created a profound impact on planetary science and exploration. The unique capability of plasma spectroscopy involving in situ elemental analysis in extraterrestrial environments, suggesting the presence of water in the red planet based on phase characterization and providing a clue to Martian paleoclimate. The key to gypsum as an ideal paleoclimate proxy lies in its textural variants, and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…An earlier study on Dergaon meteorite reported the presence of noble gases and some light elements as well [2]. At a suitable gate delay the signature of the molecular emission are also expected to be observed with LIBS [21,22]. Our experimental result reveal that the concentration of Fe and O in the present sample is in appreciable amount i.e.…”
Section: Elementssupporting
confidence: 71%
“…An earlier study on Dergaon meteorite reported the presence of noble gases and some light elements as well [2]. At a suitable gate delay the signature of the molecular emission are also expected to be observed with LIBS [21,22]. Our experimental result reveal that the concentration of Fe and O in the present sample is in appreciable amount i.e.…”
Section: Elementssupporting
confidence: 71%